DESIGNING AND MAKING authentication server DISTRIBUTED SYSTEM BASED ON XML - Yudi Irawan Chandra (JAKSTIK Journal, 2005)
Not completely secure computer networks from a variety of attacks and weaknesses of thesystem that can be exploited so that it can cause overall system failure. On the other hand,handling the security aspects of the application is still done in conjunction with thedevelopment of business processes so that the resulting system will not become effective ifthe application has many users with a variety of diverse access rights. In addition, efforts tointegrate various kinds of applications become more complex because each application has itsown method with limitations on certain platforms. Based on this background developed anauthentication server. How the authentication server is the first time by listing all theattributes In addition, registration applications must also include a list of users and accessrights. Client application then sends the user data and applications to a server identityauthentication each time a user login request. Before data is sent, the data is encrypted andthen converted to XML format. Arriving on the server, the data is then translated into textform and then decrypted into plaintext. These data are used as parameters to be validated byfirst passing the port knocking. If the validation is successful port knocking, then the specialsession will be created for that user. Then the session will be returned to the application to beprocessed further. Almost the same process also applies if the user requesting access to aprocedure. The difference lies in the validation process which involves the examination of thevalidity of the session, permissions, parameters and requirements can be met. While in thelogoff process, limit switches so that the user session is terminated can no longer perform theaccess. The existence of authentication server integration proved to facilitate a variety ofapplications under a single security system for all XML-formatted data is transferred. Inaddition, the ease of integration flexibility is also evidenced by the authentication server forcoordinating the various applications and users that use it. On the other hand, authenticationserver also serves to improve the security system shown in the form of resistance to theplaintext data reading, the man in the middle attacks and unauthorized access.